Assessing the role of anoxia as a potential extinction driver in the shallow marine Neotethys during the Permian-Triassic mass extinction - Anja B. Frank; Baran Karapunar; Stephen E. Grasby; Erdal Koşun; Niko Lahajnar; Mónica Alejandra Gómez Correa; Stella Z. Buchwald; Marc Metzke; William J. Foster (Chemical Geology, 2025)

Integrated pest management enhances biological control in a US midwestern agroecosystem by conserving predators and non-pest prey - Ivan Grijalva; Amanda R. Skidmore; Marc A. Milne; Paola Olaya-Arenas; Ian Kaplan; Rick E. Foster; John S. Yaninek (Agriculture, Ecosystems & Environment, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Identification and characterization of a novel virus associated with an eriophyid mite in extracts of fruit trees leaves - Larissa Carvalho Costa; Kristian Stevens; Xiaojun Hu; Marc Fuchs; Maher Al Rwahnih; Alfredo Diaz-Lara; Clint McFarland; Joseph Foster; Oscar P. Hurtado-Gonzales (Archives of Virology, 2021)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

The gap junction protein Cx43 is involved in the bone-targeted metastatic behaviour of human prostate cancer cells - Coralie Lamiche; Jonathan Clarhaut; Pierre-Olivier Strale; Sophie Crespin; Nathalie Pedretti; François-Xavier Bernard; Christian C. Naus; Vincent C. Chen; Leonard J. Foster; Norah Defamie; Marc Mesnil; Françoise Debiais; et al. (Clinical & Experimental Metastasis, 2012)

Planning Strategies for Community Wildfire Defense Design in Florida - Robert Brzuszek; Jason Walker; Timothy Schauwecker; Chris Campany; Marc Foster; Steve Grado (Journal of Forestry, 2010)
New community developments in the wildland-urban interface can be planned to minimize loss of property and life to wildfire through multiple defensive strategies. This research examines three communities impacted by the 1998 Florida wildfires and compares the physical context and development patterns of these communities to three recently designed Florida subdivisions that incorporate Firewise principles. Analysis of the relationship of wildfires to the physical context and development patterns of affected residential communities provides the framework by which the two groups of communities are compared. Findings show that incorporating multiple defensive strategies in community planning, including taking advantage of road location, utility corridors, greenbelts, and existing wetlands, may be effective in wildfire defense. The comparative analysis concludes with design and layout considerations for community development in the southeastern United States.

FIP/AAPS guidelines to dissolution/in vitro release testing of novel/special dosage forms - Martin Siewert; Jennifer Dressman; Cynthia K. Brown; Vinod P. Shah; Jean-Marc Aiache; Nobuo Aoyagi; Dennis Bashaw; Cynthia Brown; William Brown; Diane Burgess; John Crison; Patrick DeLuca; et al. (AAPS PharmSciTech, 2003)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)